2021
DOI: 10.1080/17517575.2021.1941275
|View full text |Cite
|
Sign up to set email alerts
|

AI-enabled Enterprise Information Systems for Manufacturing

Abstract: Research work presented in this paper considers the contemporary Enterprise Information Systems (EIS) functional architecture and carries out the literature review of AI applications integrated in Customer Relationship Management, Supply Chain Management, Inventory and logistics, Production Planning and Scheduling, Finance and accounting, Product Lifecycle Management and Human Resources, with special attention to the manufacturing enterprises. As a review outcome, the enhanced capabilities are identified in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 183 publications
(151 reference statements)
0
14
0
Order By: Relevance
“…In the field of manufacturing, a few investigations have been conducted about the collaboration and business aspect of dispersed production methods (Guan et al, 2021). That comprises reproductions of scenarios, cloud-based and production methods inspired by progress in data and CT. An alternative stream investigates dispersed producing in relation to alternate business methods and possibilities for responsive and socially produced production and consumption (Zdravković, 2022). This effort encourages small-scale, supply networks of regional socioeconomic actors to use community sources based on local area needs, resulting in ecological advantages.…”
Section: Production Processmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of manufacturing, a few investigations have been conducted about the collaboration and business aspect of dispersed production methods (Guan et al, 2021). That comprises reproductions of scenarios, cloud-based and production methods inspired by progress in data and CT. An alternative stream investigates dispersed producing in relation to alternate business methods and possibilities for responsive and socially produced production and consumption (Zdravković, 2022). This effort encourages small-scale, supply networks of regional socioeconomic actors to use community sources based on local area needs, resulting in ecological advantages.…”
Section: Production Processmentioning
confidence: 99%
“…The change developed a gap between buyer and manufacturer, restricting possibilities for personalization, the upscaling of the development, and small-scale business of data-driven items designed in the regional market. The problems established by changing customer requirements and policy changes, and the demand for new areas of expansion and improved profitability, establish a sense for rethinking the customer items production process (Zdravković, 2022). Those entails exploring ways of the current processes could be changed into more synchronized, regenerative, and regional ways of consumption and production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the era of Industry 4.0, the importance of lot-size one increases, which places high demands on workers' cognitive abilities in production and maintenance (Ansari et al 2018). In particular, flexibility, adaptability and problem-solving abilities are required (Zdravković et al 2021). The realization of comparable cognitive skills in an AI-based agent system holds immense potential for developing industrial assistance systems.…”
Section: Functional Capabilities For Ai-enhanced Assistance Systemsmentioning
confidence: 99%
“…The results showed that this method is more efficient than the traditional shipping economic evaluation model. Zdravkovic et al [ 19 ] integrated industrial Internet technology, distributed systems, cloud computing, and deep learning technology to study the application of artificial intelligence technology in enterprises. This method can realize the independent decision-making function of corporate finance.…”
Section: Introductionmentioning
confidence: 99%